Pemahaman Pedagang Pasar Sangkumpal Bonang Kota Padangsidimpuan Terhadap Ayat-ayat Dagang - Hasiah Hasiah; Shafra Shafra (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
The abstrek of this article aims at a gampse of the busyness of the Sangkumpal Bonang market traders in Padangsidimpuan who have various kinds of activities in serving consumers in fact, this profession has keep going down from their parents, adults, teenagers and children for various reasons, some just hobbies or economic demands, so they try their luck through business. Al the Sangkumpal Bonang market, traders serve consumers with various kinds of commerce, such as groceries seller, sea food, clother dealer and another, The implementation of commerce should be carried out correctly and in accordance with the rules of Islamic sharia which are slarted in the al-Qur’an. But some of traders there are doing transactions in a fraudulent way, such as mixing the types of quality gouds with unqualified. Takes some of the objects that are sold, plays with the scales and makes. The price of goods at will that is not in accordance with the standard. They did this act because of the increasing pressure of the economy so that they could not avoid cheating in trading. This situation is exacerbated by the covid-19 virus which is endemic to all corners of the world especially the city of Padangsidimpuan so that the selling values of their wares is decreasing and causing many of them so suffer losses due to the absence of consummers buying their wares. Slow down to sales of merchandise they sell. This habit is sometimes triggered by the lack of knowledge and understanding of traders about the correct Islamic rules of buying and selling as regulated in the al-qur’an. It is proper for traders in trading to reflect on the trading practices carried of by the Prophet Muhammad SAW. So that he traders without discriminating between beliefs. Therefore, the trade he carries out is known throughout the world.